Role of Preoperative Ureteral Stent on Outcomes of Retrograde Intra-Renal Surgery (RIRS) in Children. Results From a Comparative, Large, Multicenter Series. - ŞEKERCİ, ÇAĞRI AKIN (My University, 2022)
Purpose To evaluate the outcomes of pre-stented (PS) versus non-pre-stented (NPS) patients who have undergone retrograde intrarenal surgery (RIRS) for renal calculi with subgroup analysis of Asian and non-Asian cohorts. Methods Protocol is registered in PROSPERO, CRD42021261123. Eligible studies identifed from four electronic databases. Meta-analysis was done to enumerate the outcomes of RIRS in between PS and NPS. Secondary sub-analysis was done to look for diferences in outcomes in Asian and non-Asian cohorts. Results Fourteen studies involving 3831 patients (4 prospective, 10 retrospective studies) were included. PS patients experienced higher success rates of ureteral access sheath (UAS) insertion than NPS (RR 1.09, 95% CI 1.05–1.13, p<0.00001). PS patients had lower risk of ureteral injuries from UAS placement (RR 0.69, 95% CI 0.50–0.96, p=0.03). No signifcant diferences in intra- and postoperative complications between two groups were found. Stone-free rate (SFR) outcomes for residual fragment (RF) cut-of of<1 mm and<4 mm favoured the PS patients (RR 1.10, 95% CI 1.04–1.17, p=0.002 for<4 mm, RR1.10, 95% CI 1.02–1.19, p=0.02 for<1 mm). In the subgroup analysis, PS Asian patients had similar SFR as NPS patients for SFR(<4 mm) but non-Asian population showed better outcomes in the PS patients for SFR(<4 mm) (RR 1.31, 95% CI 1.13–1.52, p=0.0005). Conclusions This meta-analysis suggests that pre-stenting results in a higher success for UAS placement, minimising intraoperative ureteric injury, with higher overall SFR for any RF cut-of in PS cohorts. In non-Asian cohort, signifcant diferences occurred at SFR <4 mm but not for SFR <1 mm. No diference was seen in our Asian cohort for any SFR cut-of in both PS and NPS patients.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Pediatrik Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Pediatric Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology; Stent; Meta-analysis; Retrograde intra-renal surgery; Outcome studies; Kidney calculi; Asian